Application of International Experience in Teaching Foreign Languages in Higher Education Institutions - Ismatullaeva Iroda Izatullaevna (Genius Journals, 2022)
There have been a lot of investigations on receptive and productive skills. Being one of the receptive skills, academic reading requires a learner to make meaning from the language input. In contrast, individuals must produce both meaning and output in their own writing. Therefore, maybe, writing appears to be challenging or problematic for English language learners. This review firstly investigates the factors that affect students’ performance in writing; secondly, it examines educators’ awareness in understanding the subsistence of being listed impacts and finally it highlights some pragmatic factors which learners may encounter with while their production.
Keywords: Academic Writing; Receptive Skills; Pragmatic Awareness; Pragmatic Competence